Determinants of fertility rates in Türkiye: the role of women's income, human capital, participation in civil society and life expectancy - Burhan Durgun; Selman Kızılkaya (Discover Social Science and Health)
Abstract Fertility rates are influenced by a multitude of socioeconomic and demographic factors, including women's income, human capital, participation in civil society, and life expectancy. Understanding these dynamics is crucial in emerging economies like Türkiye, where structural inequalities and sociopolitical shifts create unique challenges and opportunities for policy intervention. This study aims to investigate the determinants of fertility rates in Türkiye, focusing on the roles of women's income, human capital, participation in civil society and life expectancy. The research utilizes annual data spanning 1990 to 2022 and applies advanced econometric methodologies, including Fourier ADL cointegration tests and Fully Modified Ordinary Least Squares (FMOLS) estimation. The findings reveal a significant nonlinear relationship between women's income and fertility rates, consistent with the fertility-income Kuznets curve hypothesis. Women's human capital and civil participation exhibit strong negative correlations with fertility. However, the negative effect of life expectancy at birth does not attain statistical significance. Together, these results highlight the interplay of income, human capital, and civil participation in shaping fertility trends, while emphasizing the need for further exploration of life expectancy's role. This study underscores the importance of addressing structural barriers to women’s human capital development and fertility reduction in Türkiye. By identifying the complex interplay of income, human capital, civil participation, and life expectancy, the research provides valuable insights for fostering inclusive and sustainable socioeconomic progress. Targeted policies promoting women's education, economic empowerment, and civil liberties are essential for achieving long-term fertility stabilization and advancing gender equality.